ANALISIS YURIDIS PENANGANAN PERKARA TINDAK PIDANA JUDI ONLINE PADA PUTUSAN NOMOR 27/PID.B/2023/PN SGR BERDASARKAN ASAS LEX SPECIALIS - Pratiwi, Dewa Ayu Putri Sukma; setianto, muhamad jodi; landrawan, i wayan (Universitas Pendidikan Ganesha, 2024)
The internet is very beneficial for life, but on the other hand the internet has a negative impact, namely as a place for crime to develop, one type of crime. One of these crimes is online gambling, where online gambling is carried out online to gain more profits for the perpetrator. Crime in cyberspace is called cyber crime. Cybercrime itself is a new form or aspect of crime that is now receiving widespread attention in the international world. The online gambling case that will be discussed in this research is decision number 27/Pid.B/2023/PN Sgr, the aim of this research is to analyze the application of law in decision number 27/Pid.B/2023/PN Sgr, to analyze the judge's considerations in decision number 27/Pid.B/2023/PN Sgr. This research uses normative juridical methods, with document study techniques, interviews and observations, with research results where the application of law in terms of the lex specialis principle is not implemented optimally in the Singaraja District Court, the judge's consideration in decision number 27/Pid.B/2023/ The Sgr District Court used Article 303 of the Criminal Code with a prison sentence of 11 (eleven) months.